2011
DOI: 10.1002/cbf.1797
|View full text |Cite
|
Sign up to set email alerts
|

CrkI and p130Cas complex regulates the migration and invasion of prostate cancer cells

Abstract: Prostate cancer metastasis is often associated with poor prognosis. The molecular coupling of the adaptor protein Crk to the docking protein p130Cas serves as a switch that regulates cell migration in several invasive cancer cells and Ack appears to act upstream of CrkII to modulate the cell motility. However, the precise role of Ack, Crk and p130Cas complex in prostate cancer migration remains unknown. In this study we examined the expression of Crk and p130Cas in prostate cancer cell lines, and found that Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Recently, many studies have reported that pro-metastatic proteins, including p130, Src and cortactin, are important for cell migration and tumor metastasis (1921). Furthermore, p130 and cortactin were originally identified as substrate proteins of the Src family kinases, and a previous report demonstrated that the MPZL1/Src/cortactin signaling cascade functions in the process of hepatocellular carcinoma cell migration (22).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have reported that pro-metastatic proteins, including p130, Src and cortactin, are important for cell migration and tumor metastasis (1921). Furthermore, p130 and cortactin were originally identified as substrate proteins of the Src family kinases, and a previous report demonstrated that the MPZL1/Src/cortactin signaling cascade functions in the process of hepatocellular carcinoma cell migration (22).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we show that both Crk and CrkL are required for cell transformation by the fos and ras oncogenes. While several prior reports emphasize the importance of Crk and CrkL in the growth of tumor cell lines, xenograft tumors and human cancers , these studies were focused on the role in the Crk and/or CrkL in the maintenance of the transformation phenotype. We induced transformation of MEF and cell lines using two well‐known viral oncogenes, v‐fos and v‐ras to investigate the effects of Crk and CrkL on the establishment of the transformed cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies primarily relied on the use of shRNA or siRNA‐based technology to reduce expression of Crk or CrkL . While these approaches have been proven effective, they can be influenced by off‐target effects .…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of p130Cas/BCAR1 has been detected in human breast, prostate, ovarian, lung, colorectal, pancreatic and hepatocellular carcinoma, as well as in glioma, melanoma, anaplastic large cell lymphoma and chronic myelogenous leukemia (Tikhmyanova et al, 2010a). Conversely, lowering the amount of p130Cas/BCAR1 expression in breast, prostate and ovarian cancer is sufficient to block tumor growth and progression of cancer cells (Cabodi et al, 2010b; Dai et al, 2011; Nick et al, 2011).…”
Section: P130cas/bcar1 and Cancermentioning
confidence: 99%